2021
DOI: 10.1186/s13002-021-00445-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical biocultural diversity by rural communities in the Cuatrociénegas Valley, Coahuila; Mexico

Abstract: Background Cuatrociénegas, part of the Chihuahuan Desert, is a region of unique biological, geological, geographical, and evolutionary importance. Its current population is mestizo; nevertheless, it has high national historical, cultural, and touristic relevance in Mexico. It has been cataloged as nationally significant for its flora and fauna by Mexican law, as well as being designated a High Protection site by the World Wildlife Fund and UNESCO. Because of its diverse and complex biological a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 69 publications
3
38
1
2
Order By: Relevance
“…The FIC index was used to measure consensus among vendors regarding the therapeutic use of each medicinal plant [ 27 29 ]. The formula is listed as follows: …”
Section: Methodsmentioning
confidence: 99%
“…The FIC index was used to measure consensus among vendors regarding the therapeutic use of each medicinal plant [ 27 29 ]. The formula is listed as follows: …”
Section: Methodsmentioning
confidence: 99%
“…(Cordero and Alejandro 2021) and Mexico (158 spp.) (Estrada-Castillón et al 2021). While other studies have recorded a smaller number of species, such as in Algeria (58 spp.)…”
Section: Resultsmentioning
confidence: 94%
“…These plant species are used for the treatment of diseases grouped under ten categories. Reported uses of various medicinal plants were compared to previously published scientific literature ( Bautista-Hernández et al, 2021 , de Rodríguez et al, 2019 , Estrada-Castillón et al, 2021 , Palacios-Espinosa et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Estrada-Castillón et al (2021) reported for the first time the UV for medicinal plants used in the Cuatro Cienegas Valley in the state of Coahuila (located 187.25 km north of the study area). The authors' results are consistent with the present study, plants such as Larrea tridentata (Sessé & Moc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation